Catalytic enantioselective intramolecular oxa-Michael reaction to α,β-unsaturated esters and amides - Su, G; Formica, M; Yamazaki, K; Hamlin, TA; Dixon, DJ (American Chemical Society, 2023)
A bifunctional iminophosphorane (BIMP)-catalyzed, enantioselective intramolecular oxa-Michael reaction of alcohols to tethered, low electrophilicity Michael acceptors is described. Improved reactivity over previous reports (1 day vs 7 days), excellent yields (up to 99%), and enantiomeric ratios (up to 99.5:0.5 er) are demonstrated. The broad reaction scope, enabled by catalyst modularity and tunability, includes substituted tetrahydrofurans (THFs) and tetrahydropyrans (THPs), oxaspirocycles, sugar and natural product derivatives, dihydro-(iso)-benzofurans, and iso-chromans. A state-of-the-art computational study revealed that the enantioselectivity originates from the presence of several favorable intermolecular hydrogen bonds between the BIMP catalyst and the substrate that induce stabilizing electrostatic and orbital interactions. The newly developed catalytic enantioselective approach was carried out on multigram scale, and multiple Michael adducts were further derivatized to an array of useful building blocks, providing access to enantioenriched biologically active molecules and natural products.